THE EFFECT OF THE SONG LYRICS “BEYOND” TO IMPROVE VOCABULARY IN READING SKILLS AT FIRST SEMESTER STUDENTS - Siti Musyarofah; Moh. Arief Wahyudi (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2026)
ABSTRACT Limited vocabulary mastery remains a major challenge for English as a Foreign Language (EFL) learners, reducing their reading comprehension and engagement with English texts. This study aimed to examine the effect of using the song lyrics of Beyond from Moana 2 on students’ vocabulary mastery in reading skills. A quantitative pre-experimental design with a one-group pre-test–post-test approach was employed. The participants were 15 first-semester students of the English Education Study Program at STKIP PGRI Bangkalan. Data were collected using vocabulary tests administered before and after the treatment and analyzed through validity, reliability, normality, and paired-sample t-test using IBM SPSS version 30. The findings revealed that the instrument was valid and reliable, while the data were normally distributed (Asymp. Sig. = 0.087 > 0.05). Students’ mean score increased from 63.33 in the pre-test to 79.33 in the post-test, indicating a statistically significant improvement after the treatment. These findings demonstrate that the song lyrics of Beyond effectively enhance vocabulary mastery in reading skills and can serve as an engaging and meaningful instructional medium for EFL learning. ABSTRAK Rendahnya penguasaan kosakata masih menjadi kendala utama bagi pembelajar English as a Foreign Language (EFL) karena berdampak pada kemampuan memahami bacaan dan keterlibatan dalam pembelajaran bahasa Inggris. Penelitian ini bertujuan menganalisis pengaruh penggunaan lirik lagu Beyond dari film Moana 2 terhadap penguasaan kosakata dalam keterampilan membaca mahasiswa. Penelitian menggunakan pendekatan kuantitatif dengan desain pra-eksperimen melalui model one-group pre-test and post-test. Subjek penelitian terdiri atas 15 mahasiswa semester pertama Program Studi Pendidikan Bahasa Inggris STKIP PGRI Bangkalan. Data dikumpulkan menggunakan tes kosakata yang diberikan sebelum dan sesudah perlakuan, kemudian dianalisis melalui uji validitas, reliabilitas, normalitas, dan Paired Sample t-Test menggunakan IBM SPSS versi 30. Hasil penelitian menunjukkan bahwa instrumen valid dan reliabel serta data berdistribusi normal (Asymp. Sig. = 0,087 > 0,05). Nilai rata-rata mahasiswa meningkat dari 63,33 pada pre-test menjadi 79,33 pada post-test, yang menunjukkan adanya peningkatan yang signifikan setelah perlakuan. Dengan demikian, lirik lagu Beyond efektif digunakan sebagai media pembelajaran untuk meningkatkan penguasaan kosakata dalam keterampilan membaca pada pembelajar EFL.